A narrative inquiry into the cultivation of EFL students’ critical thinking skills through multimodal texts - Nur Mafissamawati Sholikhah (Erudita: Journal of English Language Teaching, 2023)
This article provides a story of two female undergraduate students in learning speaking with multimodal texts to elevate their critical thinking skills. Specifically, this study tried to investigate their lived story and experience in learning with multimodal texts following with the analysis activity to foster their critical thinking skill. In addition, their perceptions towards the use of multimodality and the benefits of multimodality were also portrayed. The study was carried out in a speaking class of Foreign Language for Specific Purposes (FLSP) subject in one of private universities in Malang, East Java, Indonesia. The materials taught consisted of e-picture of advertisement shared via WhatsApp group and YouTube videos about advertisement. This study employed qualitative method with a narrative inquiry. The study findings reveal that students interviewed had positive attitudes towards learning English with multimodal texts. Moreover, the use of multimodality benefits students to raise their awareness on critical thinking. The results of study contribute to the body of knowledge regarding the use of multimodality for speaking purposes.